FROM PURDAH TO PARTICIPATION: CHANGING DIMENSIONS OF WOMEN’S PRACTICES IN INDIA - Mishra, Sudha; Kumar, Umesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The role and status of women in Indian society have undergone significant transformation from the Mughal period to contemporary India. Practices such as purdah, child marriage, and restrictions on education once defined women’s position, limiting their agency. Purdah Pratha is a traditional practice followed in many parts of India, where women were expected to cover their faces and stay out of public view, especially in front of men who were not part of their family. This practice was common in both Hindu and Muslim communities and symbolized control over women’s mobility, freedom, and participation in society. Over time, many changes have taken place in Indian society. Education, social reform movements, laws for women’s rights, and growing awareness have helped break the barriers of purdah. Women have started stepping out of traditional roles and are now seen in schools, offices, politics, and leadership positions. This paper looks at how women’s lives in India have changed from the time of Purdah Pratha to today. It discusses the struggles, the progress made, and the work still needed to ensure gender equality. The paper shows that while women have come a long way, continuous support and efforts are necessary for true empowerment and equal participation.